Influence of must yeast-assimilable nitrogen content on fruity aroma variation during malolactic fermentation in red wine. (September 2020) - Lytra, Georgia; Miot-Sertier, Cécile; Moine, Virginie; Coulon, Joana; Barbe, Jean-Christophe
Graphical abstract: Highlights: Increase in hydroxycarboxylic esters with nitrogen and malolactic fermentation. Increase in hydroxycarboxylic acid content in post-malolactic fermentation samples. Modification of fruity notes in wine post-malolactic fermentation samples. Aromatic reconstitutions prove the olfactory impact of esters. Malolactic fermentation and nitrogen levels modulate fruity aromas in red wine. Abstract: This study assessed the impact of must yeast-assimilable nitrogen (YAN) content and lactic acid bacteria (LAB) strains used for malolactic fermentation (MLF) on the formation of substituted esters, as well as the corresponding precursors (substituted acids), to investigate the modulation of fruity expression in red wines. In microvinification experiments, a Merlot must was fermented with an initial YAN content of 111 mg/L, or supplemented up to 165 and 220 mg/L. Two Oenococcus oeni LAB strains were used for MLF. Analytical methods were used to quantify substituted esters, as well as the corresponding acids, including, any enantiomeric forms. YAN supplementation of the must significantly increased concentrations of substituted esters of short- and branched-chain alkyl fatty acids produced during alcoholic fermentation (AF) (up to 67% in samples with the highest nitrogen content) and substituted esters of hydroxycarboxylic acids generated during MLF (up to 58% in samples with the highest nitrogen content). YAN supplementation in the must did not affect substituted acid formation during AF. After MLF, short- and branched-chain alkyl fatty acid levels increased in wines made from musts with the highest nitrogen content (up to 56% in samples with the highest nitrogen content), whereas concentrations of hydroxycarboxylic acids increased (up to 55%) independently of the initial YAN content, highlighting the important role of MLF. (2S)-2-hydroxy-4-methylpentanoic acid was only found in wines after malolactic fermentation, suggesting different pathways for each enantiomer and opening up new prospects for the study of bacterial metabolisms. Moreover, sensory profiles revealed a significant increase in black-berry- and jammy-fruit aromas during MLF and a strong positive correlation between these aromas and the production of substituted esters following must nitrogen supplementation and MLF. Aromatic reconstitutions revealed that variations in the concentrations of substituted esters after MLF impacted the fruity aroma of red wines.